(3EOGQI hJfejI GdCfTWI hGdbhi GdHjYjI aj GdefXeGJ GdeYGUQI (B/s - (3GdYJjHj, UHMjs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2003)
(3fTCI hJWhQ GdCfXeI GdHjYjI(B: (3GdhXGFa GdGOGQjI dEOGQI GdeHjYGJ, hXjaI JMOjO GdgOa hGdJNWjW ddCfTWI hGdbhi GdHjYjI, GdJfXje aj eLGd GdCfTWI hGdbhi GdHjYjI, GdQbGHI aj eLGd GdCfTWI hGdbhi GdHjYjI GdhXGFa GdafjI dEOGQI GdeHjYGJ(B: (3GdHjY GdTNUj, GdHjY GdJQhjLj, JfejI GdCfTWI GdHjYjI, GdGJUGdGJ GdJShjbjI GdeOeLI, GdfXGe GdSdhcj GdNdaj ddJYGed hGdeYGedI GdGOGQI GdaYGdI ddbhi GdHjYjI(B: (3GdhXGFa GdafjI dEOGQI GdeHjYGJ, JhXja Gdbhi GdHjYjI, JYhjV hecGaBJ Gdbhi GdHjYjI, JOQjH hJfejI Gdbhi GdHjYjI, GdJMajR aj eLGd Gdbhi GdHjYjI, GdGTQGa Ydi Gdbhi GdHjYjI(B.s
(3GdeQGLY U(B.289s
Keywords: (3EOGQI GdehGQOs; (3GdHjYs; (3GdJShjbs